Bogolyubov’s Approximation for Bosons - Bogolyubov (jr.), N.N.; Sankovich, D.P. (Відділення фізики і астрономії НАН України, 2010)
We analyze the approximating Hamiltonian method for Bose systems. Within the framework of this method, the pressure for the mean field model of an imperfect boson gas is calculated. The problem is considered by the systematic application of the Bogolyubov–Ginibre approximation. Проаналiзовано метод апроксимуючого гамiльтонiана для бозе-систем. У межах цього методу знайдено тиск для моделi середнього поля неiдеального бозе-газу. Задачу розглянуто за допомогою послiдовного застосування апроксимацiї Боголюбова–Жiнiбра.